The Model Pembelajaran Flipped Classroom Sebagai Upaya Peningkatan Keterampilan Berbahasa Siswa di Madrasah Ibtidaiyah - Sofianah, Monika Dewi; Sholihah, Mar’atus (MODELING: Jurnal Program Studi PGMI, 2024)
This research aims to examine the application of the Flipped Classroom learning model to improv the language skills of Madrassah Ibtidaiyah students. The approach used in this research is qualitative with descriptive methods. The data was collected through observation, interviews and documentation, and analyzed by using data reduction techniques, data presentation and drawing conclusions. The research was conducted at MI Baitul Mukmin Wringinagung with a sample of 26 grade IV students. The implementation of the Flipped Classroom learning model includes three stages: Pre-Class stage, The students study the material independently at home through videos and student assigment (LKS) books. In the In-Class stage, students engage with in-depth discussions and activities in class, with teacher guidance. The Out of Class stage involves formative evaluation to reflect student understanding. The research results showed that by implementing the Flipped Classroom model to improv students' language skills, especially in the listening and speaking aspects at MI Baitul Mukmin there was a significant increase. Previously, students experienced difficulty in understanding and determining the main idea, understanding the meaning of new vocabulary, and lacked confidence when expressing opinions and presentations due to being in a hurry and using inappropriate language. However, after implementing the Flipped Classroom learning model, 19 out of 26 students experienced significant improvements in language skills, especially in the listening and speaking aspects, with a 73% increase in their proficiency. Students are more motivated and able to understand the material better, creating a learning environment that is more interactive and effective in improv learning achievement. The average test scores of the 26 students increased from 67 to 80. Abstrak Penelitian ini bertujuan untuk mengkaji penerapan model pembelajaran Flipped Classroom dalam meningkatkan keterampilan berbahasa siswa Madrasah Ibtidaiyah. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi, wawancara dan dokumentasi, dan dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian dilakukan di MI Baitul Mukmin Wringinagung dengan sampel 26 siswa kelas IV. Penerapan model pembelajaran Flipped Classroom meliputi tiga tahapan: Tahap Pre-Class, siswa mempelajari materi secara mandiri di rumah melalui video dan buku LKS. Pada tahap In-Class, siswa terlibat dalam diskusi dan aktivitas mendalam di kelas, dengan bimbingan guru. Tahap Out of Class melibatkan evaluasi formatif untuk mencerminkan pemahaman siswa. Hasil penelitian menunjukkan bahwa dengan penerapan model Flipped Classroom dalam meningkatkan kemampuan berbahasa siswa khususnya pada aspek menyimak dan berbicara di MI Baitul Mukmin terjadi peningkatan yang signifikan. Sebelumnya siswa mengalami kesulitan dalam memahami dan menentukan gagasan pokok, memahami makna kosakata baru, serta kurang percaya diri saat mengemukakan pendapat dan presentasi akibat terburu-buru dan penggunaan bahasa yang kurang tepat. Namun, setelah penerapan model pembelajaran Flipped Classroom, 19 dari 26 siswa mengalami peningkatan yang signifikan dalam kemampuan berbahasa, terutama pada aspek mendengarkan dan berbicara, dengan persentase peningkatan mencapai 73%. Seluruh siswa lebih termotivasi dan mampu memahami materi dengan lebih baik, menciptakan lingkungan belajar yang lebih interaktif dan efektif dalam meningkatkan prestasi belajar. Rata-rata nilai ulangan 26 siswa meningkat dari 67 menjadi 80.